Drought effects on photosynthetic performance of two wheat cultivars contrasting in drought. Issue 1 (2nd January 2021) - Yang, Cheng; Zhang, Deqi; Li, Xiangdong; Shi, Yanhua; Shao, Yunhui; Fang, Baoting; Yue, Junqin; Wang, Hanfang; Qin, Feng; Cheng, Hongjian
ABSTRACT: Drought is the main factor restricting the yield of winter wheat in large arid and semiarid areas. The balance between water conservation and photosynthesis is important for breeding drought-resistant wheat cultivars. Besides, the mechanisms for drought resistance in many drought-resistant wheat cultivars have not been completely explored. To elucidate the above questions, the photosynthetic performance of drought-resistant wheat cultivar LH6 and drought-sensitive wheat cultivar ZM7698 were measured under drought treatment with different time and light intensity. The results showed that the photosystem II activity, electron transport from Q A to Q B, carboxylation and ribulose-1, 5-bisphosphate regeneration process in LH6 were inhibited less than in ZM7698 in drought conditions, which mainly contributed to the nonstomatal inhibition of photosynthesis. In normal water conditions, the transpiration rate in LH6 was higher and water use efficiency was lower than that of ZM7698, which showed no water conservation effects. In drought conditions, LH6 had a higher photosynthetic rate and stomatal conductance by maintaining the water-absorbing capacity of the roots. In conclusion, the photosynthetic apparatus of LH6 is drought resisting but costs more water; both water conservation and photosynthetic capability should be considered during breeding drought-resistant wheat cultivars in the future.